2011
DOI: 10.1634/theoncologist.2011-0101
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Meningitis from Solid Tumors: New Diagnostic and Therapeutic Approaches

Abstract: After completing this course, the reader will be able to:1. Compare the use of i.t. therapy and systemic therapies for patients with neoplastic meningitis. Describe new drugs showing promise for neoplastic meningitis.This article is available for continuing medical education credit at CME.TheOncologist.com. The Oncologist CME Program is located online at http://cme.theoncologist.com/. To take the CME activity related to this article, you must be a registered user. CME CME ABSTRACT Neuro-OncologyThe Oncologist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 78 publications
0
48
0
Order By: Relevance
“…Glial fibrillary acidic protein assessed by immunohistochemistry in CSF may facilitate the identification of malignant glial cells. 1,[63][64][65]97 Several studies have demonstrated that the sensitivity of flow cytometry is several-fold higher than that of cytology for detecting CSF leukemia or lym-phoma. 98,99 Flow cytometry allows for the early detection of neoplastic meningitis before the onset of clinical symptoms and CSF pleocytosis; therefore, its use may enable more effective treatment.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Glial fibrillary acidic protein assessed by immunohistochemistry in CSF may facilitate the identification of malignant glial cells. 1,[63][64][65]97 Several studies have demonstrated that the sensitivity of flow cytometry is several-fold higher than that of cytology for detecting CSF leukemia or lym-phoma. 98,99 Flow cytometry allows for the early detection of neoplastic meningitis before the onset of clinical symptoms and CSF pleocytosis; therefore, its use may enable more effective treatment.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…100 Future consensus regarding standardized antibody panels for flow cytometry that uniformly define positivity is likely to advance the early detection of neoplastic meningitis and will help permit its broader clinical applicability. 1,[63][64][65] Another group of researchers studied patients with epithelial cell cancers to explore how flow cytometry immunophenotyping contributed to the diagnosis and prognosis of neoplastic meningitis. 101 CSF samples from patients diagnosed with neoplastic meningitis were studied using flow cytometry immunophenotyping.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is diagnosed in 1-5 % of patients with solid tumors, 5-15 % of patients with leukemia and lymphoma, and 1-2 % of patients with primary brain tumors [2]. The most common solid tumors spreading to leptomeninges are breast cancer (43 %), lung cancer (31 %), and melanoma (6 %) [3]. Among hematologic malignancies, LMC is most commonly seen in acute lymphoid leukemia (ALL), acute myeloid leukemia (AML), and high grade lymphomas (Burkitt's, large cell) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among hematologic malignancies, LMC is most commonly seen in acute lymphoid leukemia (ALL), acute myeloid leukemia (AML), and high grade lymphomas (Burkitt's, large cell) [4]. LMC usually represents a terminal event with median survival ranging from 2 to 6 months [3]. Most untreated patients with LMC from solid tumors die within 3-6 weeks due to progressive neurologic dysfunction [3,5].…”
Section: Introductionmentioning
confidence: 99%